Development of Trigonometry's Student Worksheets Based on Microsoft Mathematics Solver for Vocational High Schools in Improving Self-Regulation Dimensions - Hidayati, Destia Wahyu; Wahyuni, Arie (Urogram Studi Pendidikan Matematika, Universitas Ivet, 2025)
PISA results show a decline in mathematical literacy scores, indicating the need for teachers to design lessons that support the understanding of mathematical concepts in various contexts and times. Although direct interaction between students and teachers is limited, it is necessary to use learning media that allows students to learn flexibly, whenever needed. The use of student’s worksheet combined with Microsoft Mathematic Solver will facilitate students' curiosity to confirm the results of the student’s worksheet that have been done self-regulationly which can be accessed anytime and anywhere. The purpose of this study was to determine the validity of the practicality of the Microsoft Mathematics Solver-based student’s worksheet on SMK Trigonometry material in increasing the self-regulation dimension in the Self-regulation Curriculum Pancasila Student Profile. This research is a development research that uses a modification of the 4D method. Validators consist of media expert lecturers, and math teachers. The instrument used is the validation sheet for the Microsoft Mathematics Solver-based student’s worksheet on SMK Trigonometry material. The data analysis technique used is the average test. The results obtained are the validity score of the Microsoft Mathematics Solver-based student’s worksheet on SMK Trigonometry material in increasing the self-regulation dimension in the Self-regulation Curriculum Pancasila Student Profile is 3.5 which is included in the valid category